(untitled) (Alternautas, 2024)
This essay is a review of and retrospective on ’Metal and Melancholy’, a 1994 documentary on taxi drivers in Lima, Peru, which effectively captures the aftermath of social, political and economic collapse. I argue the film is a window into and a warning against a possible planetary future where human beings endure through ingenuity and entrepeneurship but without the transformative tools of collective action. It also speaks to the current political crisis in Peru, which can be directly traced to the 1990s.